2011
DOI: 10.1590/s1807-59322011000200017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of a good response to initial therapy in children and adolescents with differentiated thyroid cancer

Abstract: BACKGROUND:Therapeutic approaches in pediatric populations are based on adult data because there is a lack of appropriate data for children. Consequently, there are many controversies regarding the proper treatment of pediatric patients.OBJECTIVE:The present study was designed to evaluate patients with differentiated thyroid carcinoma diagnosed before 20 years of age and to determine the factors associated with the response to the initial therapy.METHODS:Sixty‐five patients, treated in two tertiary‐care referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
2
29
0
3
Order By: Relevance
“…One of these studies found greater chances of remission in patients more than 15 years of age (26). In contrast, the other reported greater likelihood of remission in patients < 10 years of age (38). However, findings of neither study were statistically significant.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…One of these studies found greater chances of remission in patients more than 15 years of age (26). In contrast, the other reported greater likelihood of remission in patients < 10 years of age (38). However, findings of neither study were statistically significant.…”
Section: Discussionmentioning
confidence: 88%
“…Neck dissection was performed in 49 (92%) patients. Of these, modified radical neck dissection was carried out in 38 (22%) patients. Papillary and follicular histology were present in 46 (88%) and six (12%) patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Differentiated thyroid carcinoma (DTC), both papillary and follicular, is rare in pediatric patients, with an incidence between 2.6 and 12.9 % [1]. Primary treatment comprises thyroidectomy followed by radioiodine ablation and supraphysiologic doses of levothyroxine (LT 4 ) with the purpose of suppressing serum TSH and therefore inhibiting the growth of residual neoplastic tissue and preventing progression of thyroid cancer and relapse.…”
Section: Introductionmentioning
confidence: 99%
“…However, the procedure may require repetition, usually 6-12 months after the first procedure 36 . Some variables seem to influence the success of thyroid remnant ablation, and the most important one seems to be the presence of lymph node metastases 37 .…”
Section: /9mentioning
confidence: 99%